Post-Ionization Dynamics of the Polar Molecule OCS in Asymmetric Laser Fields - Endo, Tomoyuki; Ziems, Karl Michael; Richter, Martin; Fröbel, Friedrich G.; Hishikawa, Akiyoshi; Gräfe, Stefanie; Légaré, François; Ibrahim, Heide (Frontiers in Chemistry, 2022)
We have investigated the dissociation mechanisms of the prototypical heavy polar molecule OCS into the two break-up channels of the dication, OCS2+ → O+ + CS+ and OC+ + S+, in phase-locked two-color intense laser fields. The branching ratio of the breaking of the C–O and C–S bonds followed a pronounced 2π-oscillation with a modulation depth of 11%, depending on the relative phase of the two-color laser fields. The fragment ejection direction of both break-up channels reflects the anisotropy of the tunneling ionization rate, following a 2π-periodicity, as well. The two dissociation pathways in the C–S bond breaking channel show different phase dependencies of the fragment ejection direction, which are assigned to post-ionization dynamics. These observations, resulting from the excitation with asymmetric two-color intense laser fields, supported by state-of-the-art theoretical simulations, reveal the importance of post-ionization population dynamics in addition to tunneling ionization in the molecular fragmentation processes, even for heavy polar molecules.